Mathematical and Computational Modelling in Mechanics of Materials and Structures - Nicholas Fantuzzi; Francesco Fabbrocino; Marco Montemurro; Francesca Nanni; Qun Huang; José António Correia; Leonardo Dassatti; Michele Bacciocchi (Mathematical and Computational Applications)
The intersection of mathematics and computational modeling with the mechanics of materials and structural engineering continues to yield substantial advancements in both theoretical and applied domains [...]